JavaScript : absolute beginner's guide - Chinnathambi, Kirupa (Absolute beginner's guide (Indianapolis, Ind.), 2017)
"Make the most of the newest versions of JavaScript in modern web and mobile development, even if you've never used it before! This book is the freshest, fastest way to take control of JavaScript, and use it together with CSS3 and HTML5 to create powerful web and mobile experiences. You'll learn how to do what you want, the way you want, one incredibly clear and easy step at a time. Covering the latest best practices, technologies, and applications, this is the most accessible entry-level JavaScript tutorial for readers without a programming background, "--Amazon.com.